Profil Keterampilan Belajar Peserta Didik dalam Mengikuti Pembelajaran di Kelas XI SMA Negeri 5 Padang - Marzona, Rice Sri (Bimbingan dan Konseling, 2014)
This research background by the student who lack the physical and psychological readiness to learn, and out in the learning process, like storm at the time of learning and doing exercises in groups. Based on this, the researchers wanted to know: 1) resistance skills of student in learning, 2) Skills student in summarizing the book 3) Skills in the lesson notes. This research is a quantitative desriptif. Sampling was done by using simple random sampling.Populasi in this study were 367 students, while the sampled many as 37 students. Data were collected through a questionnaire to students. The research findings revealed that: 1) Skills resilience student in learning pretty well as much as 26 of the 37 student with pesentase 70.27 pesetas, 2) Skills student in the book pretty well sums up as many as 23 of the 37 students with pesentase 62.16 pesetas , 3) Skills lesson student pretty good record as many as 28 of the 37 students with pesentase 75.68 pesetas. The study recommends to student, regular follow learning activities well, teachers BK as giving guidance counseling services in schools can develop programs to improve the skills of student.